Manajemen Pondok Pesantren dalam Pembentukan Sikap Kemandirian Santri di Pondok Pesantren Hidayatul Mubatidiin Jati Agung Kabupaten Lampung Selatan - Sofyan Yahya (Departement of Mathematics Education, 2024)
Pesantren is the oldest educational institution in Indonesia. The existence of pesantren as an Islamic educational institution in the country has a very large contribution to the formation of the character of the Indonesian nation. Furthermore, the existence of pesantren from time to time has made a concrete contribution in the course of the nation's history. Formulate this research problem, namely: 1). How is the planning for the formation of an independent attitude of students at the Hidayatul Mubtadiin Islamic Boarding School? 2). How to organize the formation of an independent attitude of students at the Hidayatul Mubtadiin Islamic Boarding School? 3). How is the implementation of the formation of an independent attitude of students at the Hidayatul Mubtadiin Islamic Boarding School? 4). How is the supervision and evaluation of the formation of students' independence attitudes at the Hidayatul Mubtadiin Islamic Boarding School? This type of research is descriptive qualitative research. The data sources are the head of madrasah and their representatives, teachers, and students who were selected purposively and with snowball sampling. Data collection techniques used are observation, unstructured interviews and documentation. The conclusion of this study is that the formation of an independent attitude of students at the Hidayatul Mubtadiin Islamic Boarding School, Jati Agung District is carried out in several stages including carrying out teaching and learning activities, organization, routine mandatory activities of Islamic boarding schools, individual daily student activities, supporting activities, and boarding school discipline. . The independence of students found in the field starts from simple daily life management behaviors, such as eating, washing, and so on. Even though it is simple, if it is done repeatedly and lived as it is, it will produce a steady behavior of independence. The minimum characteristic that will be formed is in simple matters, students do not rely on other people.